Jual Beli dengan Konsep All You Can Eat dalam Pandangan Tokoh Dewan Syariah Nasional-Majelis Ulama Indonesia (DSN-MUI) - Febriana, Nina Indah; Nurfieni, Amrin (Fakultas Syariah INSURI Ponorogo, 2023)
The development of the buying and selling transaction model is inevitable, so studies in the perspective of islamic law need to continually conducted to ensure that the buying and selling transactions of society do not violate the provisions of the shari’a. buyying and selling food with the concept of “all you can eat” need to be studied because it contains provisions that are different from the concept of buying and selling food in general. The purpose of this study is to find out how the opinions of DSN MUI figures about buying and selling food with the concept of “all you can eat”. The results of this study present the views of several DSN-MUI figures regarding the practice of buying and selling with the concept of all you can eat. The provision of fines and limits on eating at all you can eat restaurants by the characters in this study is stated to be permissible with their various points of view. While the indication of gharar by some figures is stated as “gharar yasir”, and some state that the existence of gharar in buying and selling is not allowed.